2006
DOI: 10.1128/mcb.26.8.3085-3097.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Poly(A) Binding Protein C1 Binds Nuclear Pre-mRNA Poly(A) Tails

Abstract: In mammalian cells, poly(A) binding protein C1 (PABP C1) has well-known roles in mRNA translation and decay in the cytoplasm. However, PABPC1 also shuttles in and out of the nucleus, and its nuclear function is unknown. Here, we show that PABPC1, like the major nuclear poly(A) binding protein PABPN1, associates with nuclear pre-mRNAs that are polyadenylated and intron containing. PABPC1 does not bind nonpolyadenylated histone mRNA, indicating that the interaction of PABPC1 with pre-mRNA requires a poly(A) tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 62 publications
2
103
0
Order By: Relevance
“…It is therefore possible that in pab2-null fission yeast, Pab1 complements some of the essential nuclear functions normally performed by Pab2. Such a model is consistent with: (i) pab1 being a high-copy suppressor of nab2 mutant alleles in budding yeast (11) and (ii) recent data indicating that the mammalian Pab1 homolog copurifies with poly(A) polymerase and associates with intron-containing polyadenylated transcripts (71). PABP2 is required for cell viability and embryonic development in Drosophila (18).…”
Section: Discussionsupporting
confidence: 67%
“…It is therefore possible that in pab2-null fission yeast, Pab1 complements some of the essential nuclear functions normally performed by Pab2. Such a model is consistent with: (i) pab1 being a high-copy suppressor of nab2 mutant alleles in budding yeast (11) and (ii) recent data indicating that the mammalian Pab1 homolog copurifies with poly(A) polymerase and associates with intron-containing polyadenylated transcripts (71). PABP2 is required for cell viability and embryonic development in Drosophila (18).…”
Section: Discussionsupporting
confidence: 67%
“…Alternatively, the presence of pUL69 in the complex could make 4EBP1 more susceptible to phosphorylation, which would then cause its exclusion. Although primarily cytoplasmic proteins, a portion of 4EBP1 (30), eIF4E (31), PABPC1 (32,33), and pUL69 (16) are present in the nucleus, so it is possible that pUL69 prevents association of 4EBP1 with cap-associated proteins in the nucleus, even before the mRNA is transported to the cytoplasm. An interaction of pUL69 with nuclear RNAs through PABPC1 could also contribute to its role in mRNA nucleocytoplasmic transport (12).…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, the canonical poly(A)-polymerase copurifies with PABPC1, 26 suggesting the presence of PABPC1 in the vicinity of the 3' end processing complex. Consistently, a proteomic study that characterized the protein content of the mRNA 3' processing complex identified several peptides corresponding to PABPC1.…”
Section: Nuclear Role Of Pabpc1mentioning
confidence: 99%
“…First, fractionation experiments using different human cell types indicate the presence of PABPC1 in the nucleus. 26 Furthermore, cell biological experiments demonstrate that PABPC1 actively shuttles between the cytoplasm and nucleus. 27 What is the functional significance for the presence of the cytosolic PABP in the nucleus?…”
Section: Cytosolic Function Of Pabpn1mentioning
confidence: 99%